Corporate Governance in Emerging Markets : Why It Matters to Investors—and What They Can Do About It - Ararat, Melsa; Dallas, George (World Bank, Washington, DC, 2012)
What should investors do when scholarly research on corporate governance in emerging markets does not provide conclusive evidence on which aspects of governance matter most across all the emerging markets and how they affect firm performance? A researcher and a practitioner team up to offer guidelines and recommendations that focus on board independence and business group affiliation. Every day, institutional investors in emerging markets must make practical decisions on the basis of incomplete and at times conflicting information. So, it is critically important that they make the best use of this imperfect knowledge. Moreover, investors too often enter emerging markets with misguided perceptions of the underlying realities. And worse, they may cling to a conceptual framework of governance that does not allow them even to consider the searching questions they should be asking. This Private Sector Opinion, by the authors, explicitly highlights this problem. The authors identify a serious gap in research on emerging markets between high-level cross-country studies, with their inconclusive findings on good governance indicators at the macro level, and the separate effort to establish firm-level or country-specific governance metrics, typically based on what works 'in the West.' Unfortunately, less than one percent of the research papers available on corporate governance focus on emerging markets.